Intra-arterial blood pressure response in hypertensive subjects during low- and high-intensity resistance exercise - Nery, Sandra de Souza (2010)
OBJECTIVE: The aim of this study was to describe blood pressure responses during resistance exercise in hypertensive subjects and to determine whether an exercise protocol alters these responses. INTRODUCTION: Resistance exercise has been recommended as a complement for aerobic exercise for hypertensive patients. However, blood pressure changes during this kind of exercise have been poorly investigated in hypertensives, despite multiple studies of normotensives demonstrating significant increases in blood pressure. METHODS: Ten hypertensive and ten normotensive subjects performed, in random order, two different exercise protocols, composed by three sets of the knee extension exercise conducted to exhaustion: 40% of the 1-repetition maximum (1RM) with a 45-s rest between sets, and 80% of 1RM with a 90-s rest between sets. Radial intra-arterial blood pressure was measured before and throughout each protocol. RESULTS: Compared with normotensives, hypertensives displayed greater increases in systolic BP during exercise at 80% (+80±3 vs. +62±2 mmHg, P